Nonexistence of Global Weak Solutions of Nonlinear Keldysh Type Equation with One Derivative Term - Kangqun Zhang (Advances in Mathematical Physics)
We focus on the nonexistence of global weak solutions of nonlinear Keldysh type equation with one derivative term. In terms of the analysis of the first Fourier coefficient, we show the solution of singular initial value problem and singular initial-boundary value problem of the nonlinear equation with positive initial data blow-up in some finite time interval.